LHC as an axion factory: probing an axion explanation for (g - 2) [mu] with exotic Higgs decays - Bauer, Martin; Neubert, Matthias; Thamm, Andrea (Arxiv, 2017)
We argue that a large region of so far unconstrained parameter space for axion-like particles (ALPs), where their couplings to the Standard Model are of order $(0.01\!-\!1)\,TeV^{-1}$, can be explored by searches for the exotic Higgs decays